A Validated RP-HPLC-PDA with Buffer-Free Gradient Elution for Simultaneous Plasma Analysis of Trimethoprim and Sulfamethoxazole - Nicholas Edmund; Untung Gunawan; Dion Notario (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
A simple, cost-effective, and validated reversed-phase high-performance liquid chromatography (RP-HPLC) method is crucial for accurately monitoring trimethoprim and sulfamethoxazole therapy. However, conventional HPLC methods often rely on buffered mobile phases and additives, which can lead to column blockage and shorten column lifespan. To address this issue, we developed and validated a reversed-phase HPLC method with a photodiode array (PDA) detector, using a buffer-free and additive-free mobile phase with gradient elution. Sample preparation was performed using organic solvent-based deproteinization to minimize matrix effects. Chromatographic separation was performed on a ZORBAX Eclipse Plus C18 column (250 × 4.6 mm, 5 µm) using a mobile phase of acetic acid (pH 2.3), methanol, and acetonitrile at a flow rate of 1 mL/min. Detection was carried out at 270 nm with a total run time of 17 minutes. The analytical method exhibited linearity, precision, and accuracy, with adequate sensitivity for the analytes of interest. Stability testing yielded favorable results under various storage conditions, including the autosampler, freeze-thaw cycles, and long-term storage. However, the trimethoprim stock solution was only stable for two days and must be freshly prepared. Full validation was conducted in accordance with FDA and ICH bioanalytical guidelines, confirming its suitability for clinical application.